Pengaruh Kualitas Pelayanan terhadap Kepuasan Masyarakat di Kantor SAMSAT Pati - Dzurrotin Nasihah (Jurnal Akuntansi dan Pajak, 2020)
Public services are services provided by the government to the community. The services provided must be quality, directed and maximum. The SAMSAT office Pati is an agency that serves for the management of (1) Customs transfer of motor vehicle an average of 5,057 vehicles and 442 cars a month and (2) Vehicle tax totaling 8,959 units monthly and 4,289 for cars. The purpose of this study explains the empirical test results of the influence of SAMSAT service quality in Pati with indicators of attitude, speed, empathy, appearance and knowledge. The four standards are assessed by the community from the service experience obtained. This research uses a quantitative research approach. This type of research is field research. The method used is survey. Data analysis techniques used are the validity and reliability of the instrument, the classic assumption test, and the hypothesis test. Based on the calculation results F count is greater than the F table (46.392> 3.30). The results of hypothesis testing indicate that there is a significant influence between good quality (reliability, responsiveness, assurance, empathy and physical evidence) on the satisfaction of motor vehicle taxpayers in SAMSAT Pati.